Hitmen [videorecording (DVD)] - Michael, Savvas D.; Roberts, Eric, 1956-; Deacon, Adam, 1983-; St-Pierre, Georges, 1981- (LoneStar Media, 2023)
After accidentally killing the grandson of a powerful CEO, a couple are forced to fight or flee for their lives when the vengeful businessman enlists the help of a mob boss to take them down. With a